Pore fluid evolution within a hydrocarbon reservoir: Yacoraite formation (upper Cretaceous), northwest basin, Argentina - Cesaretti, Nora Noemi (2000)
Hydrocarbon and aqueous fluid inclusions in quartz and anhydrite cements in sandstones and carbonates in the upper part of the Yacoraite Formation (Upper Cretaceous) were studied in wells in the Lomas de Olmedo Sub-basin, Northwest Basin, Argentina. Intergranular, mouldic and vuggy primary porosity in these rocks was reduced by quartz overgrowths, anhydrite cement and bitumen, and was increased by dolomite recrystallization and fracturing. High porosities are thought to reflect high pore fluid pressures; the highest porosities are associated with a greater abundance of secondary fluid inclusions, reflecting healing of microfractures produced by the release of overpressured fluids. Paraffinic (light) and asphaltic (heavy to medium?) hydrocarbon fluid inclusions are recognized by their light-blue and yellow-greenish fluorescence colours. In the stratigraphically lower levels of the Yacoraite Formation, reddish-fluorescent asphaltic fluid inclusions with lower cloud points predominate, whereas in the upper levels, lighter hydrocarbons with higher cloud points, propane, ethane and methane occur in the inclusions. For aqueous fluid inclusions, data from freezing experiments indicate that NaCl-MgCl2-Na2SO4-NaHCO3-NaCO3 brines were present during cementation with 17 equiv. wt.% NaCl. Temperatures during cementation were in the range 121-137°C, indicating that the samples are in the oil and gas window. The petrographic data indicate that a hydrocarbon fluid has been present since early diagenesis began. An increase in burial depth is correlated with an increase in the temperature and pressure in the pore fluids. This caused the maturation of organic matter in the carbonates, generating CO2 and carboxyl ions, which in turn caused carbonate dissolution and anhydrite and dolomite precipitation. In the sandstones, the maturation of oil resulted in bitumen pore-fillings and secondary fluorescing inclusions.